The Expanding Interactionist Community: On the Remarkable Breadth and Depth of Symbolic Interactionism - DeGloma, Thomas (Italian Sociological Review, 2019)
Dear Colleagues, I was delighted to learn about your third Interactionist Talks meeting. Reviewing your program gave me a sense of the diverse array of interesting interactionist scholarship taking place in Italy. I regret that I was unable to attend, but offer the following reflections about the growth and health of Symbolic Interactionism. My wish is that we continue to build bridges between our respective corners of the world and expand our vibrant and growing scholarly community.